Use of proliferation cell nuclear antigen immunoreactivity for distinguishing hydropic abortions from partial hydatidiform moles. Issue 1 (January 1993) - Suresh, U R; Hale, R J; Fox, H; Buckley, C H
Abstract : AIMS: To determine whether the expression of proliferating cell nuclear antigen (PCNA) in villous cytotrophoblast could distinguish between placental tissue from a hydropic abortion and that from a partial hydatidiform mole. METHODS: Tissue from 18 partial hydatidiform moles, 15 hydropic abortions, five normal first trimester placentas and five normal full term placentas were immunostained for expression of PCNA, using the monoclonal antibody PC10. RESULTS: PCNA immunoreactivity was very much higher in the cytotrophoblast of normal first trimester placentas than in normal term placentas. Villous tissue from partial hydatidiform moles showed, on average, less immunoreactivity for PCNA than did villous tissue from hydropic abortions. CONCLUSIONS: Immunostaining for PCNA is of no value for differentiating between partial hydatidiform moles and hydropic abortions. The findings indicate that trophoblastic proliferation or hyperplasia is not a feature of partial hydatidiform moles.